The Interpretation of Quantitative and Corpus Analysis of Thematic Fields in First Collections of Short Stories by Jan Èep - Zmìlík, Richard (Bohemistyka, 2018)
The present paper is a direct continuation of the first part Potencionality of Quantitative and Corpus Analysis to Literary Studies – Toward Methodology (The Analysis of Themtic Fields), which was published in third number of this journal in 2016. In this study we present in detail the exploration of posibilities of interpretation using quantitative and corpus methods and illustrate the way, how specific we can use the results of the named metohod in the literary interpretation.